Educação 4.0 – avanços e impactos durante a pandemia - Melo, Gisele Carla Martins de (Universidade Federal Rural do Semi-Árido, 2021)
It is known that today academic life is increasingly immersed in the world of technology, and it is no different in universities. Education 4.0 has been changing the traditional way of teaching over the past few years, changing the way students teach and learn. During the Pandemic, it was necessary to adapt to the measures proposed by the government, completely changing the traditional form applied, be it public or private, everyone had to reinvent themselves. The sudden change from presential to remote classes affected the students positively and negatively. The vision and questionnaire proposed in this work aims to evaluate the main obstacles observed by them
Keywords: Ensino; Pandemia; Educação 4.0; Teaching; Pandemic; Education 4.0; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA